PENDEKATAN PERMAINAN TRADISIONAL UNTUK MENINGKATKAN HASIL BELAJAR PSIKOMOTORIK MERODA PADA SISWA KELAS VIII SMP NEGERI 2 SEMARANG - Ardha, Raditya; Kresnapati, Pandu; Juwahir, Juwahir (Journal of Physical Activity and Sports (JPAS), 2025)
This study aims to analyze the implementation of a traditional games approach in floor gymnastics learning, specifically to improve the psychomotor learning outcomes of the cartwheel movement in eighth-grade students at SMP Negeri 2 Semarang. In this study, the traditional game of "gerobak dorong" (push cart) was used as an approach to help students master the cartwheel movement. The research method employed is classroom action research with a pretest-posttest experimental group design. The research sample consisted of all 32 students from class VIII E of SMP Negeri 2 Semarang. Based on the data analysis, the results showed an improvement in the ability to perform the cartwheel movement. In cycle I, 19 out of 32 students (59%) achieved mastery, while 13 students (41%) did not. In cycle II, 27 out of 32 students (84%) achieved mastery, while 5 students (16%) did not. The results of the study indicate that the implementation of the traditional game of gerobak dorong can enhance students' psychomotor skills in performing the cartwheel movement. The improvement in cartwheel ability was 59%. Students who previously found it difficult and were afraid to perform the cartwheel movement showed significant progress after the traditional game was applied.